Risk factors for low knowledge and negative attitudes among caregivers of children with autism spectrum disorder in Iraq: a multi-centre cross-sectional study - Al-Juhaishi, Hiba Qahttan Khaleel; Jaber, Osamah Abbas; Lami, Faris; Jasim, Shatha Mohammed; Nayeri, Nahid Dehghan; Sabet, Mahdi Shafiee; Al-Gburi, Ghaith (Frontiers in Psychiatry, 2025)
IntroductionChildren with autism spectrum disorder (ASD) can experience delayed diagnosis and ineffective treatment due to low caregiver knowledge. Negative attitudes have also been linked to increased emotional problems and poor adaptive outcomes. Before educational interventions can address these issues, local knowledge and attitudes must be assessed, including the identification of high-risk groups that require prioritisation.MethodsBetween February 17 and September 10, 2024, Al-Subtain Academy for Autism and Baghdad’s National Centre for Autism and Child Psychiatry conducted a cross-sectional study. Data was collected using a structured questionnaire developed based on the Autism Stigma and Knowledge Questionnaire (ASK-Q) and a review of previous studies. The questionnaire was pre-tested on 25 caregivers for clarity and reliability.Results302 caregivers were included, all of whom were family members of the children. 57 caregivers (18.9%) had low knowledge of ASD, while only 24 (7.9%) had high knowledge. College-educated caregivers scored higher than those who were illiterate or with primary or secondary school education (p-values = 0.009, 0.002, and 0.007). Similarly, caregivers from low-income backgrounds had less knowledge than those from average and high-income backgrounds (p-value = 0.002 and 0.005). However, this difference was no longer apparent when controlling for the lack of tertiary education (B = 1.231, p-value = 0.119). 105 (34.8%) thought that a complete cure is possible, with higher rates among caregivers without tertiary education (43.0%, adjusted p-value = 0.048) or from low-income backgrounds (55.0%, adjusted p-value = 0.0002). In terms of attitudes, 44 (14.6%) believed that all children with ASD are aggressive, and 114 (37.7%) believed that they are deliberately negativistic and non-compliant. Being ashamed of the diagnosis was more common if the child had comorbid conditions. However, this difference was only significant before adjusting for multiple testing (adjusted p-value = 0.286).ConclusionEducational programmes should be implemented to enhance knowledge and address treatment expectations, especially among caregivers with low income and lower education. Efforts should be focused on reducing negative attitudes to improve overall outcomes.